2016
DOI: 10.1038/srep32064
|View full text |Cite
|
Sign up to set email alerts
|

A five-year study of the impact of nitrogen addition on methane uptake in alpine grassland

Abstract: It remains unclear how nitrogen (N) deposition affects soil methane (CH4) uptake in semiarid and arid zones. An in situ field experiment was conducted from 2010 to 2014 to systematically study the effect of various N application rates (0, 10, 30, and 90 kg N ha−1 yr−1) on CH4 flux in alpine grassland in the Tianshan Mountains. No significant influence of N addition on CH4 uptake was found. Initially the CH4 uptake rate increased with increasing N application rate by up to 11.5% in 2011 and then there was gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Seven N rates of 0, 0.5, 1, 2, 3, 6, 12, and 24 g N ∙ m −2 yr −1 of urea and seven P rates of 0, 0.05, 0.1, 0.2, 0.4, 0.8, 1.6, and 3.2 g P ∙ m −2 yr −1 of KH 2 PO 4 were applied. The determination of these application rates was based on a previous study in grassland from Bayanbulak, Xinjiang, China 40 . Treatments were laid out in a randomized block design with four replicate plots that are 3 m × 2 m size.…”
Section: Methodsmentioning
confidence: 99%
“…Seven N rates of 0, 0.5, 1, 2, 3, 6, 12, and 24 g N ∙ m −2 yr −1 of urea and seven P rates of 0, 0.05, 0.1, 0.2, 0.4, 0.8, 1.6, and 3.2 g P ∙ m −2 yr −1 of KH 2 PO 4 were applied. The determination of these application rates was based on a previous study in grassland from Bayanbulak, Xinjiang, China 40 . Treatments were laid out in a randomized block design with four replicate plots that are 3 m × 2 m size.…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall increased WFPS levels, which create appropriate conditions for anaerobic denitrification (Smith et al, 2003). Several studies have reported that an increase in soil moisture stimulates N 2 O emission (Cardoso et al, 2016;Yue et al, 2016;Zhang et al, 2014). Soil temperature and air temperature, in addition to other factors, are also commonly reported as regulators of N 2 O production.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Previous studies on the effect of N fertilization on CH 4 production or consumption have been inconclusive. Some studies have shown that N addition increases CH 4 emissions (Bodelier & Laanbroek, 2004;Mori & Hojito, 2015), stimulates CH 4 oxidation (Cardoso et al, 2019a(Cardoso et al, , 2019bZanatta, Bayer, Vieira, Gomes, & Tomazi, 2010), or has no effect (Tate et al, 2007;Yue et al, 2016). The effect of N on CH 4 emissions is probably confounded by or differs according to soil temperature and water content.…”
Section: Introductionmentioning
confidence: 99%
“…Across the studies in our dataset, the N and P treatments fell within the ranges 0 ~ 200 kg N ha ‐1 yr ‐1 and 0 ~ 200 kg P ha ‐1 yr ‐1 (Mori et al ; Zheng et al ) respectively. The non‐growing season CH 4 flux is normally not available for most field experiments, therefore, the annual rate of CH 4 uptake (kg C‐CH 4 ha −1 year −1 ) thereafter was calculated by the ratio of the growing season to non‐growing season CH 4 uptake as reported by a few studies (Li et al ; Yue et al ).…”
Section: Methodsmentioning
confidence: 99%